2020
DOI: 10.1371/journal.pntd.0008531
|View full text |Cite
|
Sign up to set email alerts
|

Dengue infection modulates locomotion and host seeking in Aedes aegypti

Abstract: Pathogens may manipulate their human and mosquito hosts to enhance disease transmission. Dengue, caused by four viral serotypes, is the fastest-growing transmissible disease globally resulting in 50-100 million infections annually. Transmission of the disease relies on the interaction between humans and the vector Aedes aegypti and is largely dependent on the odor-mediated host seeking of female mosquitoes. In this study, we use activity monitors to demonstrate that dengue virus-1 affects the locomotion and od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 87 publications
1
51
0
Order By: Relevance
“…Pathogens obtained through an infected blood meal may affect the propensity of female mosquitoes to host seek and blood feed in subsequent gonotrophic cycles, in a pathogen-specific pattern (Anderson et al 1999 ; Grimstad et al 1980 ; Koella et al 1998 , 2002 ; Platt et al 1997 ; Tallon et al 2020 ; Vogels et al 2017 ; Wekesa et al 1992 ; Yan et al 2018 ). In addition, a study by Nyasembe et al ( 2014 ) demonstrated that female An.…”
Section: The Behavioural Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…Pathogens obtained through an infected blood meal may affect the propensity of female mosquitoes to host seek and blood feed in subsequent gonotrophic cycles, in a pathogen-specific pattern (Anderson et al 1999 ; Grimstad et al 1980 ; Koella et al 1998 , 2002 ; Platt et al 1997 ; Tallon et al 2020 ; Vogels et al 2017 ; Wekesa et al 1992 ; Yan et al 2018 ). In addition, a study by Nyasembe et al ( 2014 ) demonstrated that female An.…”
Section: The Behavioural Frameworkmentioning
confidence: 99%
“…aegypti , based on larval experience, was lost following dengue virus infection. These pathogen-induced changes in vector behaviour appear to be dependent on the progression of infection within the mosquito (Anderson et al 1999 ; Koella et al 2002 ; Tallon et al 2020 ), and are often regarded as an active manipulation by the pathogen to increase transmission. However, other studies imply that these changes merely occur as a result of a general immunological response (Cator et al 2013 ).…”
Section: The Behavioural Frameworkmentioning
confidence: 99%
See 3 more Smart Citations